Chronochemistry in neurodegeneration - Pastore, Annalisa; Adinolfi, Salvatore (Frontiers in Molecular Neuroscience, 2014)
The problem of distinguishing causes from effects is not a trivial one, as illustrated by the science fiction writer Isaac Asimov in novels dedicated to an imaginary compound with surprising ‘chronochemistry’ properties. The problem is particularly important when trying to establish the aetiology of diseases. Here, we discuss how the problem reflects on our understanding of disease using two specific examples: Alzheimer’s disease and Friedreich’s ataxia. We show how the fibrillar aggregates observed in Alzheimer’s disease were first denied any interest, then to assume a central focus, and to finally recess to be considered the dead-end point of the aggregation pathway. This current view is that the soluble aggregates formed along the aggregation pathway rather than the mature amyliod fibre are the causes of disease, Similarly, we illustrate how the identification of causes and effects have been important in the study of Friedreich’s ataxia. This disease has alternatively been considered as the consequence of oxidative stress, iron precipitation or reduction of iron-sulfur cluster protein context. We illustrate how new tools have been recently developed which allow us to follow the development of the disease. We hope that this review may inspire similar studies in other scientific disciplines.